PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII5 SMP NEGERI 16 PEKANBARU - Kurnia, Isoka Amanah; ', Jalinus; Siregar, Syarifah Nur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is a class action research which aims to improve learning process and increase the mathematics learning outcomes by implying Problem Based Learning model. Subjects of this research are the students of grade VIII5 SMPN 16 Pekanbaru in the academic year 2016/2017. Total number of participant are 44, consisting of 22 male students and 22 female students with heterogeneous academic achievement. This research have two cycles, each have four stages: planning, implementation, observation, and reflection. Each cycles ended by daily examination (UH). The data collected by observation and test. The data analised by narative descriptive and statistical descriptive. The data was obtained from the observation sheets shows that teacher and students’ activities are improved after the model implemented. Students are mostly active in the learning process with the implementation of PBL, started from responding the problems presented in the early activity, discuss in groups to gain information, process the information to create a plan and solve the problems, arrange the report of discussion, presenting their works, respond to other groups’ presentation, and provide conclusions. From the data of students’ evaluation test, shows that the percentage of students who passed KKM increased from the basic score before action (38, 63%) to UH I (59,09%). Students learning outcomes also increased from UH I to UH II (68,18%). Based on the explanation above the implementation of Problem Based Learning model can improve the learning process and increase the mathematics learning outcomes for students of grade VIII5 SMP Negeri 16 Pekanbaru on odd semester of 2016/2017, of the basic competence (1.3) Understanding relations and functions. (1.4) Determine the value of functions, and (1.5) Sketching graphs of simple algebraic functions on the Cartesian coordinate plane.